ANALISIS KONDISI PEMBELAJARAN TATAP MUKA TERBATAS (PTMT) PANDEMI COVID-19 DAN MINAT BELAJAR BIOLOGI KELAS XI SMA NEGERI 1 KUNTO DARUSSALAM - Suci Ananda Fitri; Wan Syafi’i; Riki Apriyandi Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: In limited face-to-face learning (PTMT) the teacher dominates the class, the students are less involved in the teaching and learning process so that students are passive in learning. With learning methods that are different from before the co-19 pandemic, this has an impact on the lack of understanding of the material experienced by students. This has an impact on students' learning interest. This study aims to find out how the condition of limited face-to-face learning (PTMT) and interest in studying biology in class XI MIPA SMA Negeri 1 Kunto Darussalam. The research was conducted in class XI MIPA 1 and XI MIPA 2 SMA Negeri 1 Kunto Darussalam in October-November 2022. The research instrument was carried out by distributing questionnaires (questionnaires) and interviews. This study uses validity, reliability and descriptive analysis. Based on the results of the study, it was found that the limited face-to-face learning conditions (PTMT) for class XI MIPA SMA Negeri 1 Kunto Darussalam were good with an average of 71.99% and the results of interest in learning biology class XI MIPA SMA Negeri 1 Kunto Darussalam during the limited face-to-face learning period ( PTMT) pandemic covid-19 is enough with an average of 65.99%Key Word: Limited face-to-face learning (PTMT), interest in learning, Biology Learning